Petani Sebagai Panggilan Iman - Sorongan, Ferdinand Zet (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
In generaly people who lives in the village, theirs livehood is as farmer. But, there is a part ofthem is a trade (economics) wish as a secondary job from non fram. Fram is an ordinaryexperienced problem In social life not spiritual problem. In other words, from often was placebeyond of theological discussion beyond talking about God. Farmers in regions were not donethe job whole heartedly to work hard and not aware that the job wich done as a farmer is a Hisold called to glory to the God. And also priest perform as servant is not Preaching on therostrum but give motivations, urqe and want to work together without neqlect of the duty as apriest.To analyse the work of farmer as a call faith. To analyse the cause fectors of farmer when stillsurvive on their job to analsye the perceived impact by the farmer when the job was notconsidered as a call faith. From the research result was found, that the farmer’s understandingabout the job was done all this time had done so long time and become main job in sufficientfamily needs. Evidently the Experienced work of the farmer as a call faith was answered bywork hard, which is starting from plant nursery, cleaning, maintanance and processing andwhile not harvest, they looking for another jobs. But on the contrary the perceive impact of thefarmer when the job was not considered as a call faith, they are not fully to work hardwholeheartedly and earnestly for glory to God.